GEOLOGICAL AND GEOPHYSICAL INVESTIGATIONS FOR SUBSURFACE GEOLOGICAL STRUCTURES OF SOUTHERN SEMANGGOL FORMATION, GUNUNG SEMANGGOL, PERAK - OOI , WEI CHIAN (2019)
An integrated geological and geophysical study were conducted to investigate the subsurface structures of Southern Semanggol Formation at Gunung Semanggol, Perak.